Medical simulation in the education of nurses in Poland - Betke, Katarzyna; Ulenberg, Agata; Humańska, Marzena; Ponczek, Danuta; Felsmann, Mirosława (Medical Studies/Studia Medyczne, 2020)
Medical simulation is a rapidly growing branch of education of nurses in Poland. Simulation is a method used in education in order to develop students’ skills and to enable them to gain experience through an exact reconstruction of the situation using specially prepared scenarios. Simulating real events, that students may encounter in clinical practice gives the opportunity to constantly repeat the practical skills, as well as their assessment and analysis. The main purpose of medical simulation is to educate and improve patient safety. The experience of many university centres in the world shows that medical simulation training gives the opportunity to prepare better medical staff for the profession in a shorter time than traditional education. The aim of the work is an introduction to modern methods of education – medical simulation. Medical simulation training provides great educational opportunities and allows the improvement of practical skills.